IMPROVING READING COMPREHENSION ACHIEVEMENT OF THE TENTH GRADE STUDENTS OF SMA NEGERI 2 PALEMBANG BY USING ONLINE MIND MAPPING - Rani Inke Maris; Chuzaimah Dahlan Diem (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2019)
The objectives of this study were to find out (1) whether or not there was a significant improvement in reading comprehension achievement of the tenth grade students of SMA Negeri 2 Palembang after they were taught by using online mind mapping, and (2) whether or not there was contribution of each sub-skill of reading comprehension to reading comprehension achievement of the tenth grade students of SMA Negeri 2 Palembang.  In this study, Time Series design was applied. The sample of this study was 40 tenth grade students of SMA Negeri 2 Palembang, who belong to the experimental group. To collect the data, the experimental group was given a pretest and a post test. The result showed that (1). the mean difference between pre-test and post-test of the experimental group was 34.70 at the significance level of p value <0.05. Since t obtained was higher than t table (18.2111>2.023), H01 was rejected and there was a significant improvement in reading comprehension achievement after they were taught by using online mind mapping, (2).The highest contribution of reading sub-skill was given by sequence (39.4%) and then it was followed by vocabulary (23.3%), detail (17.3%), main idea (9.1%), inference (5.6%) and cause and effect (5.2%).Keywords: reading comprehension, online mind mapping